Coinfection with Schistosoma mansoni Enhances Disease Severity in Human African Trypanosomiasis - Nyambuga, Nyariki James; Mitalo, Nancy S.; Waiganjo, Naomi N.; Mokua, Mose John; Bosire, David O.; Oula, James O.; Orina, Isaac Alfred (Journal of Tropical Medicine, 2023)
Human African trypanosomiasis (HAT) and schistosomiasis are neglected parasitic diseases found in the African continent. Tis study was conducted to determine how primary infection with Schistosoma mansoni afects HAT disease progression with a secondary infection with Trypanosoma brucei rhodesiense (T.b.r) in a mouse model. Methods. Female BALB-c mice (6–8 weeks old) were randomly divided into four groups of 12 mice each. Te diferent groups were infected with Schistosoma mansoni (100 cercariae) and Trypanosoma brucei rhodesiense (5.0 ×104) separately or together. Twenty-one days after infection with T.b.r, mice were sacrifced and samples were collected for analysis. Results. Te primary infection with S. mansoni signifcantly enhanced successive infection by the T.b.r; consequently, promoting HATdisease severity and curtailing host survival time. T.b.r-induced impairment of the neurological integrity and breach of the blood-brain barrier were markedly pronounced on coinfection with S. mansoni. Coinfection with S. mansoni and T.b.r resulted in microcytic hypochromic anemia characterized by the suppression of RBCs, hematocrit, hemoglobin, and red cell indices. Moreover, coinfection of the mice with the two parasites resulted in leukocytosis which was accompanied by the elevation of basophils, neutrophils, lymphocytes, monocytes, and eosinophils. More importantly, coinfection resulted in a signifcant elevation of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin, creatinine, urea, and uric acid, which are the markers of liver and kidney damage. Meanwhile, S. mansoni-driven dyslipidemia was signifcantly enhanced by the coinfection of mice with T.b.r. Moreover, coinfection with S. mansoni and T.b.r led to a strong immune response characterized by a signifcant increase in serum TNF-α and IFN-c. T.b.r infection enhanced S. mansoni-induced depletion of cellular-reduced glutathione (GSH) in the brain and liver tissues, indicative of lethal oxidative damage. Similarly, coinfection resulted in a signifcant rise in nitric oxide (NO) and malondialdehyde (MDA) levels. Conclusion. Primary infection with S. mansoni exacerbates disease severity of secondary infection with T.b.r in a mouse model that is associated with harmful infammatory response, oxidative stress, and organ injury.
Journal Article